THE ISSUES OF ONLINE REPUTATION MANAGEMENT - A. Kosov (Вестник университета)
The increased availability of communication technologies has caused people to use the Internet to form their opinion on products and services more often. Company's reputation remains an important resource that can provide a competitive advantage, but the current information environment specificity forces us to rethink the approaches to reputation management. Сurrent specificity has conditioned by the threats concerning spontaneous information spread in the Internet, as well as the need to develop the methods of exploiting new information dissemination channels. Under these circumstances, a new competitive struggle principle has formed: «If you win in the In-ternet, you win in real life». To win, one just needs to possess the necessary technologies and to re-act to information environment changes in time. The article considers the problems of the online reputation management and the given ways of their solution.